2014
DOI: 10.1111/joic.12134
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Transulnar and Transradial Artery Access for Percutaneous Coronary Intervention in Patients with Acute Coronary Syndrome

Abstract: The TUI approach has results and access complications similar to the TRI approach and is a safe and feasible alternative for ACS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 19 publications
0
47
0
2
Order By: Relevance
“…The RCTs that compared TUA versus TRA reached different conclusions [10,16]. The largest RCT by Hahalis et al did not recommend the use of TUA as either a default or an alternative access site to TRA owing to higher access cross-over rates with TUA while other published RCTs concluded that TUA could be safely used in patients undergoing coronary procedures including primary PCI [12,17]. Therefore, to evaluate the safety and efficacy of TUA versus TRA in patients undergoing CA or PCI, we performed a meta-analysis of the available RCTs.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…The RCTs that compared TUA versus TRA reached different conclusions [10,16]. The largest RCT by Hahalis et al did not recommend the use of TUA as either a default or an alternative access site to TRA owing to higher access cross-over rates with TUA while other published RCTs concluded that TUA could be safely used in patients undergoing coronary procedures including primary PCI [12,17]. Therefore, to evaluate the safety and efficacy of TUA versus TRA in patients undergoing CA or PCI, we performed a meta-analysis of the available RCTs.…”
Section: Introductionmentioning
confidence: 93%
“…Tables I and II, respectively, show the individual study and patient characteristics, and procedural angiographic data. In two studies [10,12] abnormal Allen's or reverse Allen's test was an exclusion criteria, in another two [11,16] the patients were randomized regardless of Allen's test or reverse Allen's test results and in one study [17] there was no mention of Allen's test but they had utilized Doppler ultrasound to assess forearm vessels before the procedure. The PCI success by establishment of thrombolysis in myocardial infarction grade 3 flow was similar between two strategies in all studies.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Arterial perfusion of the wrist is provided mainly by the radial artery (RA) and the ulnar artery (UA), which are the preferred vascular access for interventional procedures . The carpal network receives an accessory contribution from the distal branches of the anterior and posterior interosseous arteries of the forearm.…”
Section: Introductionmentioning
confidence: 99%